2014
DOI: 10.3892/mmr.2014.2359
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 and BAFF: Their expression in patients with IgA nephropathy

Abstract: Since it was first described in 1968, immunoglobulin (Ig)A nephropathy (IgAN) has become the most commonly diagnosed form of primary glomerular disease worldwide. A number of reports have shown that toll‑like receptor 9 (TLR9) and B‑cell activating factor (BAFF) may be associated with IgAN; however, sufficient evidence has not yet to be delivered. In the present study, serum levels of BAFF as well as TLR9 mRNA and protein levels in peripheral blood mononuclear cells (PBMCs) were assessed. Expression of TLR9 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 31 publications
3
50
2
Order By: Relevance
“…B cell responses, including activation of intestinal B cells and RV specific IgA Ab titers were enhanced in vaccinated, probiotic colonized piglets compared to uncolonized, vaccinated piglets post-virulent human RVA challenge (Kandasamy et al, 2014). The latter effect coincided with increased TLR9 expression (see above), and according to the previous reports, TLR9 and BAFF up-regulation may be associated with increased IgA levels (Li et al, 2014), and may represent synergistic sensing of probiotics and RV by innate immune cells leading to increased IgA levels. Further, T cell responses, specifically ileal T regulatory cells, and systemic IFNγ producing T cell responses, were increased in probiotic colonized and vaccinated compared to uncolonized vaccinated piglets (Chattha et al, 2013b).…”
Section: Lactobacilli and Bifidobacteria Interactions With The Immunesupporting
confidence: 77%
“…B cell responses, including activation of intestinal B cells and RV specific IgA Ab titers were enhanced in vaccinated, probiotic colonized piglets compared to uncolonized, vaccinated piglets post-virulent human RVA challenge (Kandasamy et al, 2014). The latter effect coincided with increased TLR9 expression (see above), and according to the previous reports, TLR9 and BAFF up-regulation may be associated with increased IgA levels (Li et al, 2014), and may represent synergistic sensing of probiotics and RV by innate immune cells leading to increased IgA levels. Further, T cell responses, specifically ileal T regulatory cells, and systemic IFNγ producing T cell responses, were increased in probiotic colonized and vaccinated compared to uncolonized vaccinated piglets (Chattha et al, 2013b).…”
Section: Lactobacilli and Bifidobacteria Interactions With The Immunesupporting
confidence: 77%
“…BAFF has been recognized as a biomarker that is associated with clinical and histopathological features [43] . In our previous studies, we revealed that high levels of BAFF can promote IgA CSR and the secretion of aberrantly glycosylated IgA1 [20,26,44] . TLR3-BAFF axis, first mentioned in the field rheumatoid arthritis, has supported in vivo that TLR3-BAFF can induce AID expression and Ig class-switching in B cells [45,46] .…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood mononuclear cells (PBMCs) were isolated as previously described [26] . For urine collection, rats were immobilized above the metabolic cages.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…B‐cell‐activating factor (BAFF) and a proliferation‐inducing ligand (APRIL) are proteins of the TNF superfamily that interact through 3 receptors (BAFF‐R, TACI, and BCMA) of B cells contributing to their differentiation to memory B cells and plasma cells . High expression of both proteins has been reported in autoimmune diseases such as systemic lupus erythematosus and appears to be involved in the pathogenesis of IgAN as a stimulus for Gd‐IgA1 production . On the other hand, α‐defensins are peptides that act as effectors of innate immunity against microorganisms and also have a role on adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%